2005
DOI: 10.1007/s11269-005-6809-9
|View full text |Cite
|
Sign up to set email alerts
|

A Water Budget Model for the Yun-Lin Plain, Taiwan

Abstract: A water budget model is proposed to estimate the infiltration, runoff, evapotranspiration and recharge in vadose zone and apply to a case study. The instantaneous redistribution of infiltrated water is assumed to be uniform and a linear relationship between evapotranspiration and effective saturation is imposed. Infiltration is described by Philip's solution in conjunction with the time compression approximation method during rainfall. Runoff occurred when rainfall rate exceeds soil-infiltrating rate. The soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The results showed that the model can be satisfactorily applied to ungauged basins in the study region. Chen et al (2005) used a water budget model for the Yun-Lin Plain in Taiwan. In this model, infiltration was described by Philip's solution in conjunction with the time compression approximation method during rainfall, and the soil profile drainage was determined by evapotranspiration and recharge.…”
mentioning
confidence: 99%
“…The results showed that the model can be satisfactorily applied to ungauged basins in the study region. Chen et al (2005) used a water budget model for the Yun-Lin Plain in Taiwan. In this model, infiltration was described by Philip's solution in conjunction with the time compression approximation method during rainfall, and the soil profile drainage was determined by evapotranspiration and recharge.…”
mentioning
confidence: 99%
“…For this purpose, regional availability and volumes of groundwater resources that can sustainably be extracted for agriculture need to be evaluated. For basin scale analysis, distributed hydrological budgeting techniques (Chen et al 2005;Mazza et al 2014) and quantification methods based on remote sensing and GIS analysis (Casta et al 2010) have proved successful. For the recovery of groundwater reserves, artificial recharging techniques are widely used in industrialized countries.…”
Section: Balancing Aquifer Recharge and Dischargementioning
confidence: 99%
“…Theoretically, the groundwater equation must balance, but it is rarely happens in practice as there may be some uncertainties in the estimation of the various parameters. The amount of uncertainty can be shown as a residual term including errors in the estimation of the individual components and all minor and insignificant components neglected in the groundwater balance equation (Chen et al, 2005). For example, the aquifer system was considered as unconfined aquifer and does not account for the interflow between the layers in aquifer and includes the standing water in the surface depressions as these were prominent in the study area.…”
Section: Monthly Groundwater Balancementioning
confidence: 99%